Vaccines for COVID-19: learning from ten phase II trials to inform clinical and public health vaccination programmes. (April 2021) - Bhopal, Sunil S.; Olabi, Bayanne; Bhopal, Raj
Abstract: Public health professionals and clinicians, in many countries, are immersed in the ongoing and upcoming vaccination programmes for COVID-19. Published information from vaccine trials is complex. There are important and helpful insights about the nature of the available and forthcoming vaccines, immune responses and side-effects from phase II trials. We have systematically summarised information from 10 such trials on the nature of the vaccines, exclusions from the trials, immunological effects and side-effects. Some important information within these trial reports is not available in the phase III trial articles, so a complete picture requires examination of phase II and phase III trials for each vaccine. We recommend our systematic approach for the examination of other upcoming COVID-19 vaccine phase II and III trials.